Two-Dimensional X-Ray Diffraction (2D-XRD) and Micro-Computed Tomography (Micro-CT) Characterization of Additively Manufactured 316L Stainless Steel - Puskar Pathak; Goran Majkic; Timmons Erickson; Tian Chen; Venkat Selvamanickam (Metals)
In-depth quality assessment of 3D-printed parts is vital in determining their overall characteristics. This study focuses on the use of 2D X-Ray diffraction (2D-XRD) and X-Ray micro-computed tomography (micro-CT) techniques to evaluate the crystallography and internal defects of 316L SS parts fabricated by the powder-based direct energy deposition (DED) technique. The test samples were printed in a controlled argon environment with variable laser power and print speeds, using a customized deposition pattern to achieve a high-density print (>99%). Multiple features, including hardness, elastic modulus, porosity, crystallographic orientation, and grain morphology and size were evaluated as a function of print parameters. Micro-CT was used for in-depth internal defect analysis, revealing lack-of-fusion and gas-induced (keyhole) pores and no observable micro-cracks or inclusions in most of the printed body. Some porosity was found mostly concentrated in the initial layers of print and decreased along the build direction. 2D-XRD was used for phase analysis and grain size determination. The phase analysis revealed single phase γ-austenitic FCC phase without any detectable presence of the δ-ferrite phase. A close correlation was found between Electron Backscatter Diffraction (EBSD) and 2D-XRD results on the average size distribution and the crystallographic orientation of grains in the sample. This work demonstrates the fast and reliable as-printed crystallography analysis using 2D-XRD compared to the EBSD technique, with potential for in-line integration.